Value for health: how fortified infant cereals provide cost-effective solutions to iron deficiency anaemia in Egypt - Elmrayed, Seham; Mottaz, Sara Colombo; Dainelli, Livia; Salib, Helmy; Ghaffar, Hossam Abdel; El Gendy, Yasmin Gamal (Frontiers in Nutrition, 2025)
BackgroundAnaemia prevalence among Egyptian children under 5 years of age increased from 27.2% in 2014 to 43% in 2024, primarily attributed to iron deficiency anaemia (IDA). The World Health Organization and the United Nations International Children's Emergency Fund recommend iron-fortified foods and supplements to combat IDA. In the absence of longitudinal data among Egyptian children with anaemia, a microsimulation and cost-effectiveness analysis was conducted to evaluate the economic and health impacts of consuming iron-fortified cereals (IFC) in reducing IDA prevalence among Egyptian children under 2 years of age.MethodsData of 1707 children under 2 years of age from Egyptian Family Health Survey 2021 (EFHS) were used to create a virtual cohort of 100,000 through Monte Carlo simulations, stratified by age, gender, wealth index, and anaemia severity. A Markov model projected transitions in anaemia severity over 10 years for IFC and non-IFC consumers. Costs for IFC and home-based foods were derived from market research and existing literature, with cost-effectiveness evaluated using the incremental cost-effectiveness ratio (ICER), indicating the additional cost required to gain one additional unit of effectiveness (in our case the disability-adjusted life years [DALYs]) when two approaches are compared.ResultsThe per-day cost of home-based food was 0.37 United States Dollar (USD) per child, with an additional 0.17 USD for IFC consumers. Based on 5% IFC consumption (EFHS 2021) anaemia prevalence was projected to reduce to 32% over 10 years. DALYs averted among IFC consumers were 0.006 DALY/day and 22 DALYs over a period of 10 years. The obtained ICER of −4.14 suggests that an IFC intervention can be more effective and less costly than no intervention.ConclusionIFC interventions among Egyptian children under 2 years of age are crucial for reducing IDA. IFC consumption lowers DALYs and offers significant cost savings over 10 years, making it an effective health and economic strategy. With 4.058 million children under 2 years of age in Egypt, IFC interventions could save 7.79 million USD for 1 day of disability averted. This study provides evidence-based policy insight, urging prioritisation of IFC recommendation in public health strategies to combat IDA in children and reduce economic burdens.